1997
DOI: 10.1200/jco.1997.15.2.610
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA and antibodies to human papillomaviruses 16 E2, L2, and E7 peptides as predictors of survival in patients with squamous cell cervical cancer.

Abstract: The presence of antibodies to HPV 16 E7 proteins is of prognostic value in early-stage cervical cancer. Our results provide strong evidence that detection and typing of HPV DNA in cervical cells or tissues is not a prognostic factor for recurrence or survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…Although some studies reported a poorer prognosis if no HPV virus was detected, 9 -11 other authors came to different conclusions. [12][13][14][15][16][17] The presence of HPV type 18 has been identified as a predictor of early recurrence and poor survival. [5][6][7][8] A recent study found improved survival in patients with HPV 58 positive tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies reported a poorer prognosis if no HPV virus was detected, 9 -11 other authors came to different conclusions. [12][13][14][15][16][17] The presence of HPV type 18 has been identified as a predictor of early recurrence and poor survival. [5][6][7][8] A recent study found improved survival in patients with HPV 58 positive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] For other HPV types, the absence of detected HPV DNA sequences was reported to be associated with poor prognosis, 9 -11 whereas others found no relationship between HPV and outcome. [12][13][14][15][16][17] Most of these studies included patients who had received either surgery or a combination of surgery and radiotherapy. Although the standard treatment of locally advanced cervical cancer includes radiotherapy, little is known about the impact of HPV on the response to radiotherapy and on the patients' clinical outcome.…”
mentioning
confidence: 99%
“…23,[29][30][31] The second point concerns the differential prognostic value of HPV genotypes in invasive cancer. We 16 and others 14,22,28,[32][33][34][35][36][37][38][39][40] reported an unfavourable outcome of tumours associated with HPV18 as compared with those associated with HPV16 or with intermediate-risk HPV types. In this work, based on the analysis of a larger number of cases with a long follow up, the better outcome of tumours associated with intermediate-risk HPV was confirmed, but the respective prognostic value of HPV18 vs. HPV16 showed little differences.…”
Section: Discussionmentioning
confidence: 99%
“…17 All HPV negative cases were reviewed histologically to confirm the diagnosis and to check the representative character of the tissue specimens. The corresponding DNA preparations were further analyzed by AMPLICOR HPV test (Roche Molecular Systems, Inc, Branchburg, NJ) that utilizes amplification of target DNA by PCR followed by nucleic acid hybridization for the detection of 13 high-risk HPV types (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68). 18 Samples that were found positive with GP51/GP61 primers and/or AMPLICOR HPV test but negative for HPV type 16, 18, 33, 45, 6 and 11 were then HPV genotyped by reverse hybridization using the Roche Linear Array genotyping test (Roche Molecular Systems, Inc, Branchburg, NJ) that identifies 37 different anogenital HPV DNA genotypes.…”
Section: Patientsmentioning
confidence: 99%
“…También se ha encontrado utilidad de la determinación de RNAm y DNA de HPV en pacientes con cáncer cervicouterino por su asociación con el pronóstico de la enfermedad (44,45,46), y de la determinación de anticuerpos contra HPV en pacientes con cáncer cervicouterino como predictores de sobrevida (47).…”
Section: Investigación Actual Y Futuraunclassified